Management of Choronic Plantar Ulcers in Leprosy by Flap Surgery - B.K. Rath; B.K. Das; J.M. Das; P.P. Kumar (Indian Journal of Plastic Surgery)
Thirty three cases of chronic plantar ulcers due to leprosy were treated by flap surgery and the result analysed. It was observed that local skin flap were suitable for small defects especially in the forefoot. Muscle flaps were most suitable for ulcers of heel. The best procedure currently available to reconstruct ulcers in the weight bearing areas was provided by myocutaneous flaps. Fascio-cutaneous flaps were found useful for covering large defects. Cross-leg and Cross-foot flaps were not suitable for weight-bearing areas and were associated with prolonged immobilisation.